I am trying to understand a step in the answer to a differential equation which has initial condition: $i_0 = i(t=0)$

$$\frac{di} i + \frac{di}{1-i} = \beta\langle k\rangle \, dt$$

integrate both sides to obtain

$$\ln i - \ln(1-i) + C = \beta\langle k \rangle t $$

Using the initial condition of $i_0 = i(t=0)$, we get:

$$ i = \frac{i_0 e^{\beta \langle k \rangle t}}{1-i_0 + i_0 e^{\beta \langle k \rangle t}} $$

That is the correct answer. However, I am having difficulty moving from line 2 ie $$\ln i - \ln(1-i) + C = \beta\langle k \rangle t $$

Firstly, I am trying to justify the value of C using the initial condition. If i substitute into the second line, I get:

$$ \ln \left\lvert\frac{i}{1-i}\right\rvert + C = \beta \langle k \rangle(0) $$ so, $$ \ln\left\lvert\frac{i}{1-i}\right\rvert + C = 0 $$ $$ \ln\left\lvert\frac{i}{1-i}\right\rvert + C = 0 $$ I am not even sure if I am on the right track. I would appreciate some suggestions on how to proceed.

  • $\begingroup$ You are on the right track (although it should be $i_0$ instead of $i$ in the last equation). Hence, $C = -\ln\tfrac{i_0}{1-i_0}$. Putting this into the equation that you have for $i$ gives $\ln\tfrac i{1-i} = \beta t+\ln\tfrac{i_0}{1-i_0}$. Now, use the exponential function on both sides and go on with Donald's answer. $\endgroup$ – amsmath Sep 10 '18 at 23:55

\begin{eqnarray*} \frac{i}{1-i}= \frac{i_0}{1-i_0} e^{\beta(k)t} \end{eqnarray*} Now multiply both sides by$(1-i)(1-i_0)$ and make $i$ the subject of the formula.


You have $$\ln\lvert\frac{i_0}{1-i_0}\rvert + C = 0$$

Solve for $C$ and substitute in

$$\ln i - \ln(1-i) + C = \beta\langle k \rangle t$$ to get $$\ln i - \ln(1-i) - \ln\lvert\frac{i_0}{1-i_0}\rvert = \beta\langle k \rangle t$$

Combine the logarithms and solve for $i$ to get the final answer.

  • $\begingroup$ When I combine the logarithms and apply e to both sides I get $$\frac{i}{1-i}\times \frac{i_{0}}{1-i{0}} = e^{\beta \langle k \rangle t}$$ From there I get: $$\frac{i}{1-i} = \frac{1-i{0}}{i_{0}} e^{\beta \langle k \rangle t}$$ I see where @DonaldSplutterwit has something a bit different. He has: $$\frac{i}{1-i} = \frac{i_{0}}{1-i{0}} e^{\beta \langle k \rangle t}$$. Why is that. $\endgroup$ – niz Sep 11 '18 at 1:04
  • $\begingroup$ you should get $\frac{i}{1-i}\times \frac{1-i_{0}}{i{0}} = e^{\beta \langle k \rangle t}$ $\endgroup$ – Mohammad Riazi-Kermani Sep 11 '18 at 1:10
  • $\begingroup$ thank you, i see that. silly oversight. I appreciate you patience. $\endgroup$ – niz Sep 11 '18 at 1:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.